A Slave's Tale - Haugaard, Erik Christian (Book collections on Project MUSE., 2013)
A Slave's Tale, the sequel to Hakon of Rogen's Saga, is told from the point of view of a slave girl, Helga, who stows away on the longship when Hakon, the young Viking chieftain, sets sail for France on a voyage to return Rark, a freed slave, to his homeland. The voyagers' journey is perilous--they narrowly escape capture by an invading fleet, and their ship is severely damaged by a storm. Upon reaching France--where the Vikings are now hated, not feared--only tragedy ensues.